The influence of gender roles in the drivers of luxury consumption for women: Insights from the gulf region. (November 2019) - Semaan, Rania W.; Lindsay, Val; Williams, Paul; Ashill, Nick
Abstract: Luxury consumption is a complex phenomenon that has been shown to convey prestige, signal wealth, boost self-esteem, and express self-concept and identity. Many of the earlier studies have been conducted in Western societies, and lack a detailed understanding of how culture and demographics such as gender may influence such consumption. In this exploratory study, we unravel the complexity further, and explore the drivers of luxury consumption among Gulf Arab women. Utilizing focus groups comprising 31 Gulf Arab females, we gain a deeper understanding of luxury consumption and evaluate the respective drivers in this context. Grounded in social role theory, we find a striking contrast between our results and the drivers of Gulf Arab female luxury consumers as predicted by extant theory. Specifically, Gulf Arab women displayed a number of independent and agentic behaviors in their luxury consumption, which contrasts to their social role in the Gulf Arab society that is often more communal and interdependent. We suggest a number of theoretical and practical implications from our study.